Study on Electric Motor Vibration Suppression by Active Dynamic Vibration Absorber - Okada, Takeshi; Isobe, Makoto; Kosaka, Takashi; Steinmann, Paul; Matsumori, Hiroaki; Matsui, Nobuyuki (2023 IEEE International Electric Machines and Drives Conference, IEMDC 2023, 2023)
This paper presents a study on an active dynamic vibration absorber (DVA) to reduce the vibration and acoustic noise generated from electric motors for variable speed drives. As a DVA is just additional components, miniaturization and cost reduction are expected by reducing the number of parts and high reliability owing to lifetime prolongation thanks to its jointless structure. In addition, a variable stiffness function can be realized as an active DVA by equipping with an actuator. This study aims to realize the isolation and suppression of the multiple vibration resonances that inherently come from the electric motor being operated over a wide speed range. As a prototype hybrid excitation flux switching motor for automotive traction drive is dealt with as an example of target electric machines, an active DVA is designed sequentially along with the proposed design scheme using FEA and topology optimization. Finally, its usefulness for motor vibration suppression is demonstrated through FEA-based simulation and experiments using DVAs fabricated by 3D printing.
CRIS-Team Scopus Importer:2023-10-06
Keywords: dynamic vibration absorber; hybrid excitation flux switching motor; motor vibration suppression; variable speed drive; variable stiffness